2021
DOI: 10.1101/2021.06.02.446716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A female-specific role for Calcitonin Gene-Related Peptide (CGRP) in rodent pain models

Abstract: We aimed to investigate a potentially sexually dimorphic role of Calcitonin Gene-Related Peptide (CGRP) in mouse and rat models of pain. Based on findings in migraine where CGRP has a preferential pain-promoting effect in female rodents, we hypothesized that CGRP antagonists and antibodies would attenuate pain sensitization more efficaciously in female than male mice and rats. In hyperalgesic priming induced by activation of interleukin 6 (IL-6) signaling, CGRP receptor antagonists, olcegepant and CGRP8-37, bo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
3
1
0
Order By: Relevance
“…Moreover, a clinical meta-analysis of anti-CGRP signaling treatments for nausea in episodic migraine provided strong support for their effectiveness 33 . Interestingly, we also observed that female mice were more severely affected by systemic CGRP than their male counterparts, which correlates with preclinical studies showing stronger tactile sensitivity in female mice when challenged with durally applied CGRP 34 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, a clinical meta-analysis of anti-CGRP signaling treatments for nausea in episodic migraine provided strong support for their effectiveness 33 . Interestingly, we also observed that female mice were more severely affected by systemic CGRP than their male counterparts, which correlates with preclinical studies showing stronger tactile sensitivity in female mice when challenged with durally applied CGRP 34 .…”
Section: Discussionsupporting
confidence: 87%
“…(Table 2). This sexual dimorphism is similar to higher incidence of migraine and VM in female patients 4,38,39 and reports of sexual-dimorphic effects of CGRP both in dura-induced pain, spinal cord neuropathic pain, and preclinical surrogate of allodynia or touch sensitivities 34 . To this end, other studies have demonstrated a sex difference in the expression of CGRP receptor components in the trigeminal nucleus 40 .…”
Section: Cgrp Signaling and Murine Motion-sickness Indicessupporting
confidence: 80%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted June 16, 2021. ; https://doi.org/10.1101/2021.06.15.447407 doi: bioRxiv preprint induces pain hypersensitivity only in females in rodent preclinical models of migraine 68 . Recent developments show that this female-specific effect of CGRP may be dependant on prolactin 69 and involves KCC2-dependent disinhibition 70 . Further studies are needed to understand the role of CGRP in mediating the hyperexcitability of SDH neurons in males and females.…”
Section: Discussionmentioning
confidence: 99%